Dairy farmers’ information management and software use: a study case in Florida, Uruguay - Álvarez, J. (Agrociencia Uruguay, 2003)
During 2000, October and November, a study involving 61 Florida dairy farmers was done. The main purpose of the study was to understand the farmer’s management information practices and their opinions about the potential of computing information technology use. The data collected allowed measuring a large variability of information management procedures and systems. Within the three information areas evaluated, financial, animal nutrition, and livestock management, informal systems, based on unstructured records, and farmer’s memory abilities; formal manual systems; computerised systems; and service systems, usually linked with an advisory relationship, were found. Secondly, it was also found differences on farm and farmer’s characteristics, which may act as potential explanatory variables of farmer’s information management styles. These included farm size, farmer age, experience, and formal education, management style, time devoted on farm management tasks, and the extent of consultant involvement in farm decision making. Farm computers were mainly used to assist livestock management, while financial and animal nutrition showed few developments. Additionally, more than a third of the interviewed farmers stated their satisfaction with their current information management. Finally, an important percentage of farmers reported their information management weaknesses. In order to improve their information systems, some of them decided to uptake computerised technology, improve the farm information management, use of advisory services and more demand of information.